Implementing AI-integrated English writing: university English language learners writing strategies and perceptions - Yong-Jik Lee; Seung-Hoon Jeong (Institute of Advanced Engineering and Science, 2026)
This study examines the writing strategies and perceptions of Korean university English language learners (ELLs) regarding the integration of generative artificial intelligence (AI) in their writing process. A total of 85 university students participated by completing surveys and participating in in-depth interviews. The findings indicated that ELLs predominantly employed writing strategies such as brainstorming, translating from their first language (Korean), and using digital tools, particularly translation apps, for revision and feedback. Students perceived AI tools positively, noting significant cognitive and emotional benefits, including enhanced vocabulary, grammar learning, and increased writing confidence. However, ELLs expressed concerns regarding ethical issues, potential dependency on AI, and the risk of reduced human interaction. The study advocates for incorporating generative AI as a supplementary instructional resource within English as a foreign language (EFL) writing education, emphasizing the need for careful instructional design to foster independent critical thinking and effective writing practices. The research offers practical insights for English language teaching (ELT) educators who utilize AI technology to support EFL learners while upholding academic integrity and student autonomy.